2010
DOI: 10.1902/jop.2010.100190
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Periodontal Disease and Osteoporosis in Postmenopausal Women in Jordan

Abstract: Osteoporosis was significantly associated with severe alveolar crestal bone loss and the prevalence of periodontitis cases in postmenopausal Jordanian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
77
3
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 36 publications
19
77
3
5
Order By: Relevance
“…30 The association between systemic BMD and periodontal disease has been addressed in a number of studies. 6,[9][10][11][12][13][14][15][16][17][18][19][20] While the cross-sectional studies conducted on post-menopausal osteoporotic females and elderly males suggested that there was a correlation between systemic BMD and periodontal disease, [9][10][11]14,35 other studies conducted on pre-menopausal females and young male populations did not support such a relationship. 6,12,13 A recent longitudinal study conducted on elderly Chinese males suggested that osteoporosis is associated with severe loss of clinical attachment and interproximal gingival recession.…”
Section: Discussionmentioning
confidence: 95%
“…30 The association between systemic BMD and periodontal disease has been addressed in a number of studies. 6,[9][10][11][12][13][14][15][16][17][18][19][20] While the cross-sectional studies conducted on post-menopausal osteoporotic females and elderly males suggested that there was a correlation between systemic BMD and periodontal disease, [9][10][11]14,35 other studies conducted on pre-menopausal females and young male populations did not support such a relationship. 6,12,13 A recent longitudinal study conducted on elderly Chinese males suggested that osteoporosis is associated with severe loss of clinical attachment and interproximal gingival recession.…”
Section: Discussionmentioning
confidence: 95%
“…Progressive systemic bone loss could have significant dental implications. Papers addressing the relationships among osteoporosis, estrogen deficiency and periodontitis have been published [2,3,6,[20][21][22][23]. It has been suggested that estrogen deficiency may be a risk factor for tooth loss [3,13,24,25], might affect dental implant success or compromise osseous support in totally edentulous subjects, leading to difficulty in wearing dentures.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of estrogen levels observed in women after the menopause results in accelerated bone loss, and can lead to osteoporosis. Since osteoporotic changes have been observed in oral bone [2][3][4][5][6][7], and loss of alveolar bone is a prominent feature in periodontal diseases, osteoporosis may play a significant role in the progression of periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Deficijencija estrogena posle menopauze i gubitak koštane mineralne gustine pokazali su da mogu biti povezani sa povećanom stopom gubit ka zuba. Ovi odnosi se mogu objasniti povećanom težinom parodontopatije kod defi -cijencije estrogena 40,41 . Pokazalo se da su ukupni kalcijum tela i koštana gustina usko povezani sa koštanom gustinom donje vilice.…”
Section: Osteoporozaunclassified
“…Nedavni epidemiološki i klinički podaci daju ograničene, ali uverljive dokaze, koji sugerišu povezanost između osteoporoze i parodontopatije. Mnogi zajednički faktori rizika mogli bi biti otkriveni u nastanku oba oboljenja 41,42 . Sistemska osteoporoza razvija se usled gubitka kosti i dovodi do lomljenja kostiju.…”
Section: Osteoporozaunclassified